Impact of extracellular‐to‐intracellular fluid volume ratio on albuminuria in patients with type 2 diabetes: A cross‐sectional and longitudinal cohort study. Issue 7 (28th November 2020) - Nakajima, Hanako; Hashimoto, Yoshitaka; Kaji, Ayumi; Sakai, Ryosuke; Takahashi, Fuyuko; Yoshimura, Yuta; Bamba, Ryo; Okamura, Takuro; Kitagawa, Noriyuki; Majima, Saori; Senmaru, Takufumi; Okada, Hiroshi; et al.
Abstract: Aims/Introduction: Body fluid volume imbalance is common in patients with kidney failure, and is associated with all‐cause mortality. This study aimed to investigate the association between fluid volume imbalance and albuminuria in patients with type 2 diabetes mellitus without kidney failure. Materials and Methods: Using data from one cohort study, a baseline cross‐sectional study of 432 participants and a longitudinal cohort study of 368 participants who could follow up was carried out. Body fluid imbalance was determined by measuring the extracellular water (ECW)‐to‐intracellular water (ICW) ratio (ECW/ICW) using bioelectrical impedance analysis. A change in the urinary albumin‐to‐creatinine ratio (ACR) was defined as the ratio of urinary ACR at follow up to that at baseline. The ECW/ICW ratio was compared with the level of albuminuria. Results: In this cross‐sectional study, the ECW/ICW ratio increased with the level of albuminuria. There was an association between the ECW/ICW ratio and logarithms of urinary ACR after adjusting for covariates (β = 0.205, P < 0.001). Furthermore, the ECW/ICW ratio was associated with a change in the urinary ACR after adjusting for covariates (β = 0.176, P = 0.004) in this longitudinal study. According to the receiver operating characteristic curve, the optimal cut‐off point of the ECW/ICW ratio for incident macroalbuminuria, defined as ACR >300 mg/gCr, was 0.648 (area under the curve 0.78, 95% confidence interval 0.58–0.90). Conclusions: The ECW/ICW ratio is independently associated with the level of albuminuria in patients with type 2 diabetes mellitus without kidney failure. This reinforces the importance of monitoring fluid balance in patients with type 2 diabetes mellitus. Abstract : Fluid imbalance occurred in diabetes patients without kidney failure, and was associated with the level of albuminuria. The extracellular water to intracellular water ratio is independently associated with changes in albuminuria in patients with type 2 diabetes mellitus without kidney failure. Clinicians need to pay more attention to monitoring the fluid status among patients with type 2 diabetes mellitus, and maintaining fluid balance in the early stage of diabetic kidney disease.